Effectiveness of Religious Extracurricular Activities in Enhancing Students’ Spirituality: A Case Study of SMP Negeri 23 Makassar - Ramlianto, Ramlianto; Pewangi, Mawardi; Miro, Abbas Baco (FKIP - Universitas Riau, 2025)
This study examines the effectiveness of religious extracurricular activities in enhancing students’ spirituality at SMP Negeri 23 Makassar. The background of this research lies in the phenomenon of students’ low spiritual awareness and limited participation in religious activities, despite the presence of Islamic education in formal classes. The purpose of this study is to analyze how extracurricular programs can improve students’ spiritual practices, moral behavior, and social awareness through structured non-formal education. A qualitative descriptive approach was applied, with data collected through observation, interviews, and documentation involving students, extracurricular mentors, Islamic education teachers, and school leaders. Data were analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing). The results show that activities such as Qur’an recitation, congregational prayers, sermon training, and Islamic commemorations have significantly enhanced students’ worship habits, discipline, politeness, and social concern. The active role of teacher-mentors as role models and the school’s institutional support emerged as key factors for success, while limited time and unequal student participation remain challenges. In conclusion, religious extracurricular activities proved effective in enhancing students’ spirituality, indicating that non-formal programs are essential to strengthen character education in inclusive public schools.